What are the physiologic effects of Resistance Exercise behind breast cancer-related lymphedema prevention? - Roldán-Jiménez, Cristina (Elsevier, 2023)
Research in the last decades’ haven driven a paradigm shift in the approach to physical activity and exercise prescription in breast cancer survivors. Clinical guidelines have moved from bedrest dogma and avoiding strenuous activity in the upper limb to recommending resistance exercise (RE). In recent years, scientific evidence has shown that RE in the upper extremities can even have a preventive effect on breast cancer-related lymphedema (BCRL). This knowledge was achieved thanks to systematic reviews with meta-analyses analyzing variables related to RE programs on lymphatic response and volumetry. However, other variables related, such as inflammation or acute responses, have been less addressed. The hypothesis presented in this paper is that there are both acute and chronic inflammatory and lymphatic response to exercise, systemic effects such as arm volume and body composition changes and unknown physiologic mechanics which contribute to BCRL prevention.
Keywords: Mamas -- Cáncer; Fisioterapia; Breast cancer; Exercise; Lymphedema; Rehabilitation; Resistance exercise